Comparisons between tumor burden and other prognostic factors that influence survival of patients with non‐small cell lung cancer treated with immune checkpoint inhibitors. Issue 12 (3rd November 2019) - Sakata, Yoshihiko; Kawamura, Kodai; Ichikado, Kazuya; Shingu, Naoki; Yasuda, Yuko; Eguchi, Yoshitomo; Hisanaga, Jumpei; Nitawaki, Tatsuya; Iio, Miwa; Sekido, Yuko; Nakano, Aiko; Sakagami, Takuro
Abstract: Background: The use of baseline tumor burden (TB) as a prognostic factor for non‐small cell lung cancer (NSCLC) patients treated with immune checkpoint inhibitors (ICIs) and associations between TB and other prognostic biomarkers remain unclear. In this study, we investigated the association between TB and survival in NSCLC patients treated with ICIs in comparison with other biomarkers. Methods: We retrospectively evaluated 83 NSCLC patients with ICIs administered between February 2016 and December 2018. TB was measured as the sum of the unidimensional diameters of up to five target lesions. Results: The median observation period was 14.2 months. A total of 42 patients died during the follow‐up. Univariate Cox regression analysis showed that baseline TB was associated with OS. Cox regression analysis adjusted for Eastern Cooperative Oncology Group performance status (ECOG PS) alone or with addition of programmed cell death ligand 1 expression and treatment line showed that TB was a prognostic factor for OS. Using time‐dependent receiver operating characteristic curve analysis, the optimal TB cutoff for predicting OS was 12 cm, and patients were divided into a high TB group ( n = 21) and a low TB group ( n = 62). The low TB group achieved significantly longer OS than the high TB group (median OS: 18.5 months, [95% CI = 11.7‐not reached] vs. 2.3 months [95% CI = 1.3–2.9], P < 0.001). Conclusion: TB is a useful, clinically measurable prognostic factor of survival in NSCLC patients treated with ICIs.